2014
DOI: 10.3126/jkmc.v2i4.11774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes of Ultrasonic technique (Harmonic Focus™) with Conventional technique in open hemithyroidectomy

Abstract: Background: The option for dissection and haemostasis during thyroid surgery include either the modern ultrasonic technology (Harmonic Focus™) or the conventional technique using knot and ties, monopolar or bipolar electrocautery. Comparison between the surgical outcomes of open hemithyroidectomy using these two modalities was done.Objective: To compare the surgical outcomes of ultrasonic technique using Harmonic Focus™ (HS) with Conventional technique (CT) in open hemithyoidectomy.Method: Twenty consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Till date there is only one study in Nepal that compares the efficacy of ultrasonic based device with the conventional techniques. 8 In addition in this study the patients undergoing sub-total, near and total thyroidectomy were also compared. …”
mentioning
confidence: 99%
“…Till date there is only one study in Nepal that compares the efficacy of ultrasonic based device with the conventional techniques. 8 In addition in this study the patients undergoing sub-total, near and total thyroidectomy were also compared. …”
mentioning
confidence: 99%
“…12 Regmi et al showed that thyroidectomy by ultrasonic technique resulted in less intraoperative blood loss by 16 ml than in conventional thyroidectomy. 26 Rienzo et al showed in their series that intraoperative blood loss was comparable when they used a harmonic scalpel and Liga Sure vessel sealing device and significantly less than in the conventional clamping and knot-tying technique. 27 And all authors reported that the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…20 In contrary to the recommendations, many centers in Nepal and India, antibiotics are being prescribed for various duration following thyroidectomy. [4][5][6] In an international survey among endocrine surgeons, the patterns of antibiotic use varied widely among European, American and Asian surgeons. Most of the Asian surgeons (58.3%) almost always prescribed antibiotic prophylaxis in contrary to European surgeons whereby only 8.8% do so routinely.…”
Section: Discussionmentioning
confidence: 99%
“…4 In most of the centers in Nepal, perioperative antibiotics are still administered for varying duration. 5,6 At Patan Hospital, Nepal, study regarding use of antibiotic prophylaxis has not been done in thyroid surgery, but, a study on low risk laparoscopic cholecystectomy, regarded as clean surgery, routine use of antibiotic prophylaxis did not show added advantage in preventing SSI. 7 There is a dearth of literature regarding antibiotic prophylaxis in our set up.…”
Section: Introductionmentioning
confidence: 99%